Can you really swim? Validation of self and parental reports of swim skill with an inwater swim test among children attending community pools in Washington State. Issue 4 (12th January 2016) - Mercado, Melissa C; Quan, Linda; Bennett, Elizabeth; Gilchrist, Julie; Levy, Benjamin A; Robinson, Candice L; Wendorf, Kristen; Gangan Fife, Maria Aurora; Stevens, Mark R; Lee, Robin
Abstract : Background: Drowning is the second leading cause of unintentional injury death among US children. Multiple studies describe decreased drowning risk among children possessing some swim skills. Current surveillance for this protective factor is self/proxy-reported swim skill rather than observed inwater performance; however, children's self-report or parents' proxy report of swim skill has not been validated. This is the first US study to evaluate whether children or parents can validly report a child's swim skill. It also explores which swim skill survey measure(s) correlate with children's inwater swim performance. Methods: For this cross-sectional convenience-based sample, pilot study, child/parent dyads (N=482) were recruited at three outdoor public pools in Washington State. Agreement between measures of self-reports and parental-reports of children's swim skill was assessed via paired analyses, and validated by inwater swim test results. Results: Participants were representative of pool's patrons (ie, non-Hispanic White, highly educated, high income). There was agreement in child/parent dyads' reports of the following child swim skill measures: 'ever taken swim lessons', perceived 'good swim skills' and 'comfort in water over head'. Correlation analyses suggest that reported 'good swim skills' was the best survey measure to assess a child's swim skill—best if the parent was the informant (r=0.25–0.47). History of swim lessons was not significantly correlated with passing the swim test. Conclusions: Reported 'good swim skills' was most correlated with observed swim skill. Reporting 'yes' to 'ever taken swim lessons' did not correlate with swim skill. While non-generalisable, findings can help inform future studies.